2023
DOI: 10.1177/03000605221148833
|View full text |Cite
|
Sign up to set email alerts
|

Perception of COVID-19-related stigma and associated psychological challenges among healthcare workers at Cairo University hospitals

Abstract: Objectives The current study explores the level of perceived social stigma and associated psychological challenges among healthcare workers during the second wave of the COVID-19 pandemic in Egypt. Methods This was a cross-sectional study of 150 healthcare workers at Cairo University hospitals that were confirmed positive for COVID-19 infection. Participants were interviewed for assessment of perceived COVID-19-related stigma and associated psychological symptoms using the Patient Health Questionnaire for depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(76 reference statements)
1
7
0
Order By: Relevance
“…Negative consequences were reportedly experienced by COVID-19 patients with anxiety being the most common, 18,19,23,27,40,43,49,53,58,62,69,86,91 followed by depression, 18,23,32,43,49,53,58,62,69,91 reduction of socialization, 22,37,39,4547,66,80 fear, 31,45,58,66,76,87,89 distress, 19,52,63,75 anger, 40,50,58,76 mental health disorders, 19,47,58,90 secondary traumatic stress, 30,49 non-disclosure of COVID-19, 35,56 reluctance to test/seek care, 38,47 loss of financial support, 36 loss of accommodation, 46 helplessness, 40 loneliness, 40 burnout, 30 l...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Negative consequences were reportedly experienced by COVID-19 patients with anxiety being the most common, 18,19,23,27,40,43,49,53,58,62,69,86,91 followed by depression, 18,23,32,43,49,53,58,62,69,91 reduction of socialization, 22,37,39,4547,66,80 fear, 31,45,58,66,76,87,89 distress, 19,52,63,75 anger, 40,50,58,76 mental health disorders, 19,47,58,90 secondary traumatic stress, 30,49 non-disclosure of COVID-19, 35,56 reluctance to test/seek care, 38,47 loss of financial support, 36 loss of accommodation, 46 helplessness, 40 loneliness, 40 burnout, 30 l...…”
Section: Resultsmentioning
confidence: 99%
“…The review findings indicated there were various outcomes experienced by participants, such as anxiety which was the most experienced one, 18,23,27,40,43,49,53,58,62,69,88,91 followed by depression, 18,23,32,43,49,53,58,62,69,91 fear, 31,45,58,66,76,88 anger, 19,40,50,60,76,87,89 mental health disorders, 19,47,49,58,90,91 secondary traumatic stress, 30,53,62,63,76 non-disclosure of COVID-19, 25,35,47,56,80,89 loss of financial support, 36,73,80 burnout, 30 less happiness, 27 insomnia, 27 losing business, 29 changed interpersonal relation, 29,66 psy...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the response to COVID-19, frontline health workers are inevitably at risk of SARS-CoV-2 infection ( 7 , 14 16 ). They have a 3.4 times higher risk of contracting COVID-19, a higher risk of death compared to people living in the general community ( 17 , 18 ). The fear of being infected is significant and related to the perceived risk of lethality.…”
Section: Introductionmentioning
confidence: 99%